STRATEGI PEMASARAN USAHA TAHU TEMPE DI KECAMATAN MANDIANGIN TIMUR DALAM PERSPEKTIF EKONOMI ISLAM - Ningsih, Nurul Widhiya; Rafidah, Rafidah; Putriana, Marissa (Gapenas Publisher, 2025)
This study discusses the sharia marketing strategy implemented by tofu and tempeh entrepreneurs in Mandiangin Timur District to increase sales. This research method uses a qualitative research type with a descriptive approach. Data were obtained through observation, interviews and documentation. The results of the study indicate that the strategy implemented by tofu/tempeh businesses in Mandiangin Timur District is a marketing mix, namely a mix of product, price, promotion and location determination. Consistent product quality, such as hygiene and innovation, is key to attracting and retaining consumers. Flexible pricing allows entrepreneurs to adapt to market conditions, while promotions that utilize social media and traditional methods help expand market reach. Choosing a strategic location also plays an important role in distribution efficiency and business sustainability. From an Islamic economic perspective, the marketing strategy of tofu and tempeh businesses in Mandingin Timur District applies Islamic marketing and the principles of Islamic marketing, namely shiddiq (honest), amanah (trustworthy), fatanah (intelligent/leadership) and tabligh (communication).